Fear of hypoglycemia and its clinical significance: a case-control study - Elena Georgievna Starostina; Elena Nikolaevna Moshnyaga (Сахарный диабет, 2013)
Aim. To assess the prevalence of fear of hypoglycemia, its clinical features and influence on diabetes compensation. Materials and Methods. A cross-sectional study was conducted with 200 sequentially enrolled participants with type 2 diabetes mellitus (T2DM; n=139) and type 1 diabetes mellitus (T1DM; n=61). Patients were screened for psychiatric disorders with appropriate inventory and examined by a psychiatrist. Subjects identified as those with fear of hypoglycemia (n=12) formed the study group, while control group was assembled of individuals without phobic signs, matched for gender, age, type and duration of diabetes and concomitant psychiatric disorders. Results. Prevalence of fear of hypoglycemia was estimated at 6%, being consistently higher in patients with T1DM (16.1%) vs. T2DM (1%; p=0.0002). Fear of hypoglycemia was associated with higher median HbA1c (9.4% [8.6 ; 9.9] vs. 8.2% [6.8 ; 9.3], p